The role of the multidisciplinary team in palliative care in the elderly (Research, Society and Development, 2021)
The objective of the research was to analyze multidisciplinarity in care from the perspective of each professional who works in the health of the elderly. This is an exploratory-descriptive field study with a quantitative and qualitative approach. The data collection was carried out with health professionals who work in the health of the elderly in Greater João Pessoa-PB from April to May 2021. The health professionals of the João Pessoa-PB network were interviewed according to their professional performance in the area of health of the elderly. Data collection was carried out through a semi-structured interview script that involves the following aspects: palliative care, termination, limitations and experiences, through the Google Forms platform. Regarding the sample, 85% are women, 60% are between 20 and 39 years old, 65% are married and 75% are Catholic. All responded that they know about palliative care, 60% of those involved have already participated directly in some action related to the subject and 70% of the professionals use this care in their elderly patients. For most of those surveyed, palliative care seeks to alleviate the suffering of the patient, being able to facilitate understanding and acceptance of the disease, as well as the appreciation of what can still be experienced. Regarding teamwork, some weaknesses are still observed among family members and professionals, as well as among the members of the multidisciplinary team. It was possible to weigh the importance of the comprehensiveness and humanization of care by health professionals when addressing the personal vision of the care provided.